Psychoanalysis - Delgado, Honorio (1918)
An unfortunate and lamentable exclusiveness had prevented take citizenship card psychiatry as a science of the last century. On one hand, in the case of neurosis, which remained more or less recognized as products of psychological activity, why is not sought, coherence, causality, in its own sphere, as is done in science with all manner of phenomena but they were considered as failures of any psychological meaning. The problem was resolved in the negative, or rather, it was assumed nonexistent. The symptoms of hysteria were not at that time pre scientific than the result of an incongruous imagination. Furthermore, with regard to psychosis, awoke the enthusiasm method exploits pathology, especially with the discovery of certain brain locations was due, without further examination, somatógena conception as the only way to be accepted into the study of psychosis. The weather has been commissioned to prove their sterility. Mal could indeed deduced scientific phenomena formula belonging to the psychopathological scale were evaluated on the scale cerebropática.